2020
DOI: 10.1039/d0fo00787k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined calcium and vitamin D supplementation on osteoporosis in postmenopausal women: a systematic review and meta-analysis of randomized controlled trials

Abstract: The aim of the present study was to explore whether combined calcium and vitamin D supplementation is beneficial for osteoporosis in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 45 publications
5
59
0
5
Order By: Relevance
“…Although SD is a broad range of vitamin D indicator, the long SD group was associated with a lower occurrence of osteoporosis in our study. This finding is consistent with previous studies exploring the links of vitamin D obtained via dietary intake or supplementation, serum 25(OH)D, and sunlight exposure with BMD, osteoporosis, or fractures [20,21,23,33]. One experimental study using rats reported that PTH was significantly reduced in the sun-exposed vitamin D-deficient group (67.69 ± 13.18 pg/ml) compared to the levels in the vitamin D-supplemented rats (78.93 ± 8.31 pg/ml) and vitamin D-deficient rats (86.05 ± 9.67 pg/ml) [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although SD is a broad range of vitamin D indicator, the long SD group was associated with a lower occurrence of osteoporosis in our study. This finding is consistent with previous studies exploring the links of vitamin D obtained via dietary intake or supplementation, serum 25(OH)D, and sunlight exposure with BMD, osteoporosis, or fractures [20,21,23,33]. One experimental study using rats reported that PTH was significantly reduced in the sun-exposed vitamin D-deficient group (67.69 ± 13.18 pg/ml) compared to the levels in the vitamin D-supplemented rats (78.93 ± 8.31 pg/ml) and vitamin D-deficient rats (86.05 ± 9.67 pg/ml) [22].…”
Section: Discussionsupporting
confidence: 93%
“…An increasing number of studies are being conducted on the association between vitamin D and BMD. However, the intake of vitamin D alone is not evident to prevent fractures [ 18 , 19 ]; instead, review studies have suggested that combining vitamin D with calcium intake is associated with a lower risk of osteoporosis and fractures [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect was not observed at the femoral neck or lumbar spine. These observations are in agreement with a recent meta-analysis demonstrating a beneficial effect of VitD supplements and enriched foods, along with calcium, on BMD and reduction in fragility fractures in postmenopausal women [33].…”
Section: Discussionsupporting
confidence: 92%
“…Diet is a significant modifiable factor involved in the occurrence and progression of chronic metabolic diseases, such as osteoporosis [1]. Previous studies have shown that the risk of osteoporosis is related to the intake of multiple nutrients, including minerals such as calcium [2] and zinc [3], vitamins such as vitamin D [4] and vitamin K [5], and other nutrients [6,7]. Many researchers have also found that adherence to specific dietary patterns, such as the Mediterranean diet [8,9], is associated with a lower risk of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%